Synovial cyst of the thoracic spine: case report Cisto sinovial da coluna torácica: relato de caso - Helio A. Oliveira; Alan Chester F. de Jesus; Roberto César P. Prado; Augusto César E. Santos; Paulo Marcelo S. Sobral; Arthur Maynart P. Oliveira; Sonia Maria L. Marcena; Douglas Rafaele A. Silveira (Arquivos de Neuro-Psiquiatria)
Spinal cord compressing syndrome due to synovial cyst (SC) of the thoracic spine is a rare clinic condition. We report a case of SC located in the thoracic spine causing spastic paraparesis in a 14 year-old female patient. The SC was removed thoroughly by laminectomy. The patient had an excellent recovery. The etiological and therapeutic aspects are discussed. Síndrome de compressão medular causada por cisto sinovial (CS) da coluna torácica é patologia rara e pouco descrita na literatura. Descrevemos um caso de CS da coluna torácica causando paraparesia espástica em uma paciente de 14 anos de idade. O cisto foi removido através de laminectomia e a paciente apresentou uma excelente recuperação. Discutimos os aspectos etiológicos e terapêuticos.